UPF Harmonic Current Detection Based Shunt Active Filter for Harmonic Reduction - S. Prabakaran, K. Saravanan, P. Ram Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In modern distribution systems the proliferation of large power electronic systems results in increased harmonic distortion. Harmonic distortion results in reduction of power quality and affects the system stability. The harmonics extraction is based on the unity power factor (UPF) theorem in time domain to calculate the reactive power compensation in the power system. The switching control algorithms of the proposed UPF based shunt active filter manages to generate appropriate switching gates to the active power filter. The intention of this method is to compensate reactive power and reduce the unwanted harmonics. The simulation of the system is done using MATLAB-SIMULINK and finally, the proposed detection method is applied to shunt active power filter and to be implemented in PIC16F8777A microcontroller